Frequency of presentation of symptoms of depression, anxiety and stress following the coronavirus pandemic in students of the Medicine of the Universidad Abierta Interamericana Interamerican Open University - Rosario Campus - Alvarado Baissetto, Facundo; Filippini, Dr. Fernando; Alvarado Baissetto, Dr. Thomas (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: The COVID-19 pandemic has caused alterations in the mental health of university students, its impact has generated the appearance of symptoms of depression, anxiety and stress due to confinement and the adoption of virtual education. Objective: To describe the frequency of symptoms of depression, anxiety and stress after the coronavirus pandemic in students of the Medical School of the Universidad Abierta Interamericana (UAI)- Sede Rosario. Materials and methods: Quantitative, descriptive, observational, cross-sectional and retrospective study, carried out at the UAI, during the period from December 2022 to May 2023. The population consisted of students from fourth to sixth year of the Medical Career. The sample was non-probabilistic by convenience. The instrument for data collection was the DASS-21 Scale, which consists of 21 questions related to depression, anxiety and stress. The variables age, sex, current year and symptoms of depression, anxiety and stress were analyzed. Absolute and relative frequencies were calculated. Results: Sixty students were surveyed, of whom 32 (53%) were female and 28 (47%) male. The mean age was 24.31 ± 7.01 years (min: 18; max: 40), with a higher frequency in the population under 25 years of age. Twenty students from each year analyzed (4th, 5th and 6th years) were considered. A high frequency of anxiety (90%), depression (87%) and stress (82%) was found. Thirty-seven percent of sixth year students presented higher frequency of anxiety, depression and stress in some of their levels, followed by fifth year with 35% and fourth year with 29%. Conclusions: Symptoms of depression, anxiety and stress were more frequent in female students under 25 years of age who were in their last years of medical school